2024
DOI: 10.15407/economyukr.2021.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Державне Регулювання Як Чинник Протидії Covid-19

Abstract: The most successful fight against COVID-19 is demonstrated by countries with effective state institutions, which have become absolutely critical when confronting SARS-CoV-2: from quarantine restrictions, equipping hospitals and providing financial assistance packages to national economies to developing COVID vaccines, deployment of their production and mass vaccination of the population until the formation of collective immunity. These countries are not only centers of highly adaptable business, but also of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Ukrainian economist, Prof. S.O. Korablin in his study concludes that government regulation has become a key factor in transforming COVID vaccines into the public good (Korablin, 2021).…”
Section: Government and Its Role In Modern Market Economymentioning
confidence: 99%
See 1 more Smart Citation
“…Ukrainian economist, Prof. S.O. Korablin in his study concludes that government regulation has become a key factor in transforming COVID vaccines into the public good (Korablin, 2021).…”
Section: Government and Its Role In Modern Market Economymentioning
confidence: 99%
“…Moreover, during the reforms and hard times (e.g., global financial crisis -2009) the effectiveness of state governance, the quality of public administration, and the success of quickly implemented policies are appeared to be the key factors in confronting a wide variety of domestic and international problems, many of which are not only of economic origin (e.g., Korablin, 2021;Report, 2011;Bryant & Sigurjonsson, 2022;Honcharenko et al, 2020;Halasiuk, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, in the Council Resolution of 23 April 1996 aimed at implementing the basic principles of industrial policy for the EU pharmaceutical sector EU [22], set out in the 1994 Commission Communication [21], the EU leadership drew attention of the member states to the importance of the link between policies to control costs in the health sector and measures to ensure the competitiveness of national pharmaceutical industries [21] 10 . 20 years ago, the document "Pharmaceutical industry: a strategic sector in the European economy" [23] outlined the industry development priorities to be implemented during 2014-2020 in the framework of "Horizon 2020" 11 and the EU Structural Funds for 2014-2020. However, despite the strong position of European producers on the global market, the COVID-19 pandemic hit the sector harder than any other economic shock in EU history.…”
Section: Key Aspects Of the Eu Policy That Determine The Industry's D...mentioning
confidence: 99%
“…10 The basic principles of industrial policy on pharmaceuticals were identified as: encouraging innovation through a competitive market and changes in the regulatory framework; protecting new medicines by intellectual property rights, both in the EU and in third countries; ensuring the availability of medicines that provide better health protection for European citizens; promoting research on innovative therapies of particular relevance to public health and encouraging research on rare diseases and the development of appropriate medicines. 11 The Innovative Medicines Initiative (IMI) has become one of the flagships of Horizon 2020 health research, a public-private partnership in the life sciences between the EU and the European pharmaceutical industry.…”
Section: Key Aspects Of the Eu Policy That Determine The Industry's D...mentioning
confidence: 99%
See 1 more Smart Citation